Inhibition of Akt/mTOR/p70S6K Signaling Activity With Huangkui Capsule Alleviates the Early Glomerular Pathological Changes in Diabetic Nephropathy - Wu, Wei; Hu, Wei; Han, Wen-Bei; Liu, Ying-Lu; Tu, Yue; Yang, Hai-Ming; Fang, Qi-Jun; Zhou, Mo-Yi; Wan, Zi-Yue; Tang, Ren-Mao; Tang, Hai-Tao; Wan, Yi-Gang (Frontiers in Pharmacology, 2018)
Huangkui capsule (HKC), a Chinese modern patent medicine extracted from Abelmoschus manihot (L.) medic, has been widely applied to clinical therapy in the early diabetic nephropathy (DN) patients. However, it remains elusive whether HKC can ameliorate the inchoate glomerular injuries in hyperglycemia. Recently the activation of phosphatidylinositol-3-kinase (PI3K)/serine-threonine kinase (Akt)/mammalian target of rapamycin (mTOR) signaling and its downstream regulator, 70-kDa ribosomal protein S6 kinase (p70S6K), play important roles in the early glomerular pathological changes of DN including glomerular hypertrophy, glomerular basement membrane (GBM) thickening and mild mesangial expansion. This study thereby aimed to clarify therapeutic effects of HKC during the initial phase of DN and its underlying mechanisms. Fifteen rats were randomly divided into 3 groups: the normal group, the model group and the HKC group. The early DN model rats were induced by unilateral nephrectomy combined with intraperitoneal injection of streptozotocin, and administered with either HKC suspension or vehicle after modeling and for a period of 4 weeks. Changes in the incipient glomerular lesions-related parameters in urine and blood were analyzed. Kidneys were isolated for histomorphometry, immunohistochemistry, immunofluorescence and Western blotting (WB) at sacrifice. In vitro, murine mesangial cells (MCs) were used to investigate inhibitory actions of hyperoside (HYP), a bioactive component of HKC, on cellular hypertrophy-associated signaling pathway by WB, compared with rapamycin (RAP). For the early DN model rats, HKC ameliorated micro-urinary albumin, body weight and serum albumin, but had no significant effects on renal function and liver enzymes; HKC improved renal shape, kidney weight and kidney hypertrophy index; HKC attenuated glomerular hypertrophy, GBM thickening and mild mesangial expansion; HKC inhibited the phosphorylation of Akt, mTOR and p70S6K, and the protein over-expression of transforming growth factor-β1 in kidneys. In vitro, the phosphorylation of PI3K, Akt, mTOR and p70S6K in MCs induced by high-glucose was abrogated by treatment of HYP or RAP. On the whole, this study further demonstrated HKC safely and efficiently alleviates the early glomerular pathological changes of DN, likely by inhibiting Akt/mTOR/p70S6K signaling activity in vivo and in vitro, and provided the first evidence that HKC directly contributes to the prevention of the early DN.